MENINGKATKAN KETERAMPILAN SUMBER DAYA MANUSIA DENGAN TANAMAN HIDROPONIK - Melinda Shofari Fauzi Awaliyah; Rabiyanur Lubis; Akmal Riski Gunawan Hasibuan (LPPM Universitas Islam 45, 2022)
The emergence of economic problems that occurred as a result of the Covid-19 pandemic, it is necessary to increase the skills of human resources through trainings that can educate the public in order to increase the cost of living for the community. One form of training that can be done is by educating hydroponic plants. The method used in this community service is training and counseling about hydroponic plants. The results of this research are that residents can understand and practice how to grow hydroponic plants